Context Matters, but How Much? Latent state–trait analysis of cognitive ability assessments. (September 2016) - Hermes, Michael; Stelling, Dirk
Abstract : Cognitive abilities are thought to represent temporally stable constructs, however, accumulating evidence suggests that effects of the measurement situation could affect its measurement (e.g., effects of test motivation, stress level). The present study modeled these effects explicitly in a latent variables approach. In contrast to previous studies, we investigated participants (job candidates) in repeated high‐stakes settings ( N = 188). We found that cognitive ability measurements in high‐stakes settings not only reflect a stable latent trait and random measurement error, but also systematic effects of the test setting. Our results support the application of cognitive ability tests in organizational contexts but have implications for its use in applied settings such as personnel selection.